A Prussian blue positive electrode material and preparation method thereof, and battery

By covering the hydrophobic cladding layer on the surface of the core material of the Prussian blue positive electrode material, the problem of easy water absorption after removing moisture is solved, the effect of low water content and preventing secondary water absorption is achieved, the battery cell processing cost is reduced and the battery performance is improved.

CN117457902BActive Publication Date: 2025-03-28NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311785188.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-25
Publication Date
2025-03-28
Estimated Expiration
2043-12-25

AI Technical Summary

Technical Problem

Prussian blue cathode materials tend to absorb water after removing moisture, resulting in increased battery cell preparation costs and reduced battery performance.

Method used

By covering a hydrophobic cladding layer on a part of the core material, the contact angle between the material and water is increased, moisture adsorption is reduced, and the conversion process of surface adsorption water to internal crystallization water is interrupted.

Benefits of technology

A Prussian blue cathode material with low water content is realized, which prevents secondary water absorption, reduces battery cell processing costs, and improves battery circulation performance and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117457902B_ABST
    Figure CN117457902B_ABST
Patent Text Reader

Abstract

The present invention provides a Prussian blue positive electrode material and a preparation method thereof, and a battery. The Prussian blue positive electrode material includes a core material and a coating layer coated on at least part of the surface of the core material: the coating layer includes one or more of polysiloxane, ethyl silicone oil, methylphenyl silicone oil, wax-containing silicone oil, cyanide-containing silicone oil, and phosphate surfactants; wherein the Prussian blue positive electrode material has a single crystal morphology, and the mass ratio of the coating layer to the core material is (0.005-0.05): 1. The present invention increases the contact angle between the material and water and reduces the moisture adsorption on the surface of the material by adding a hydrophobic coating layer; at the same time, the coating layer interrupts the conversion process of surface adsorbed water to internal crystallized water, so that the Prussian blue composite material not only has a low water content, but also can prevent it from secondary water absorption during use, so that it reaches a moisture growth value of no more than 600ppm after being exposed to water absorption for 72 hours at a dew point of -20°C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a Prussian blue positive electrode material and a preparation method thereof, and a battery. Background Art

[0002] Sodium Prussian blue does not require sintering during its synthesis and can be directly synthesized using the co-precipitation method. It does not contain precious metals and is environmentally friendly. As a battery positive electrode material, it has received widespread attention due to its lowest cost.

[0003] However, due to the charge balance effect of the Prussian blue compound, M′(CN)6 holes are easily generated in the crystal structure. These holes are often occupied by water molecules, which are called coordinated water. Crystallization water is also inevitably present in the pores within the crystal structure. Crystallization water does not participate in the coordination of transition metals but exists alone in the pores. It also forms hydrogen bonds with the coordinated water, which requires higher energy to break the hydrogen bonds when removing the crystallization water, making it more difficult to completely remove the water. In addition, when the internal holes and pores are filled, some adsorbed water will also exist on the surface. Due to the existence of holes, the material is also very easy to absorb water after water removal.

[0004] Therefore, according to the difficulty of different types of water in the Prussian blue compound to escape, coordinated water > crystallization water > adsorbed water, the order of water loss can be attributed to first removing the surface adsorbed water, then the crystallization water, and finally the coordinated water; conversely, when the water is completely removed, the material is exposed to an environment with high moisture and its water absorption order can be regarded as the reverse behavior of the water loss order, that is, the water absorption process is a gradual transition from surface adsorbed water to internal crystallization water and coordinated water, and after entering the bulk phase, it exists preferentially in the form of coordinated water.

[0005] In the prior art, adsorbed water is often removed by using a blast oven at low temperature. This method can only remove surface adsorbed water and a portion of crystal water in the structure. Therefore, before assembling the battery, the pole piece needs to be treated in a vacuum oven at high temperature and for a long time to remove the crystal water and coordinated water inside the positive electrode material structure. At the same time, on this basis, an assembly environment with a lower dew point condition needs to be provided to avoid secondary water absorption of the positive electrode material in the pole piece during the battery cell assembly process, which greatly increases the cost of battery cell preparation.

[0006] Therefore, how to provide a Prussian blue composite material that can easily remove surface adsorbed water and prevent the material from secondary water absorption during use has always been the goal pursued by scholars in the industry. Summary of the invention

[0007] The present invention provides a Prussian blue-based cathode material, a preparation method thereof, and a battery. By coating a hydrophobic coating layer on at least a part of the surface of the core, the contact angle between the material and water is increased, and the water adsorption on the material surface is reduced. At the same time, the coating layer interrupts the conversion process of surface adsorbed water to internal crystal water, so that the Prussian blue-based composite material not only has a low water content value, but also can prevent secondary water absorption during use, so that the water content increase value does not exceed 600 ppm after being exposed to water absorption at a dew point of -20°C for 72 hours.

[0008] For this reason, the first object of the present invention is to provide a Prussian blue-based cathode material;

[0009] The second object of the present invention is to provide a preparation method of a Prussian blue-based cathode material;

[0010] The third object of the present invention is to provide a battery;

[0011] To achieve the first object of the present invention, the present invention provides a Prussian blue-based cathode material, which includes a core material and a coating layer coated on at least a part of the surface of the core material: the chemical formula of the core material is A x M[M′(CN)6] 1–y •□ y •zH2O, where A is an alkali metal ion; M and M′ are transition metal ions; □ is a [M′(CN)6] 3- / 4- hole; z-H2O is coordinated water; 0 < x ≤ 2; 0 < y ≤ 0.25; 0 ≤ z ≤ 5; the coating layer includes one or more of polysiloxane, ethyl silicone oil, methyl phenyl silicone oil, wax-containing silicone oil, cyanide-containing silicone oil, and phosphate surfactants; wherein, the Prussian blue-based cathode material has a quasi-single crystal morphology, and the mass ratio of the coating layer to the core material is (0.005 - 0.05):1.

[0012] Compared with the prior art, the technical effects achieved by adopting this technical solution are as follows: the water absorption process of the Prussian blue-based cathode material gradually transitions from surface adsorbed water to internal crystal water and coordinated water. Among them, the water molecules occupying the hole positions are called coordinated water; the water molecules in the pore channels within the crystal structure are called crystal water, and the crystal water will form hydrogen bonds with the coordinated water, resulting in a higher energy required to break the hydrogen bonds when removing the crystal water, increasing the difficulty of completely removing water;

[0013] Therefore, the Prussian blue positive electrode material of the present application includes a core material and a coating layer. By constructing a uniform and dense coating layer on the surface of the core material, on the one hand, the contact angle between the material and water can be increased to reduce surface moisture adsorption; on the other hand, the dense coating layer interrupts the conversion process of surface adsorbed water to internal crystalline water, thereby reducing the internal crystalline water content; the dew point requirement for moisture in the storage / packaging space is reduced, and a small amount of adsorbed water on the surface can be removed by using a lower temperature during the electrode drying stage, without considering the impact of the difficulty in removing internal crystalline water on battery performance, thereby effectively reducing the pressure on the cell end to process the electrode water content and achieving a reduction in processing costs.

[0014] Furthermore, the coating layer includes one or more of polysiloxane, ethyl silicone oil, methylphenyl silicone oil, wax-containing silicone oil, cyanide-containing silicone oil, and phosphate surfactants. On the one hand, since the above materials have hydrophobic and waterproof properties, coating the surface of the core material can make its positive electrode material waterproof and hydrophobic, increase the contact angle between the material and water, and reduce the adsorption of moisture on the surface of the material; on the other hand, the use of these coating materials will be evenly coated on the surface of the particles to form a uniform and dense hydrophobic oligomer coating layer. Due to the micro-nano structure characteristics of its surface, the tiny air shield layer hinders the contact between moisture and the core material, thereby interrupting the conversion process of surface adsorbed water to internal crystallized water, so that the crystallization water content of the material is kept within a low range.

[0015] In Prussian blue positive electrode materials, the mass ratio of the coating layer to the core material is (0.005-0.05): 1. The hydrophobic coating layer accounts for a low proportion in the Prussian blue positive electrode materials and does not affect the specific structure of the Prussian blue positive electrode materials, so that they still maintain a quasi-single crystal structure. The Prussian blue positive electrode materials hinder the contact between moisture and the surface of the core material through a tiny air shield layer, thereby preventing the material from absorbing water secondary to use, and does not affect the electrochemical properties of the Prussian blue positive electrode materials.

[0016] In one technical solution of the present invention, A in the core material includes Li + 、Na + , K + and / or the core material M and M' include Fe 2+ , Fe 3+ 、Ni 2+ , Mn 2+ , Mn 3+ 、Co 3+ 、Zn 2+ , Cu 2+ Cr 3+ Cr 4+and / or the material used for the coating layer includes one or more of polysiloxane, ethyl silicone oil, methylphenyl silicone oil, wax-containing silicone oil, cyanide-containing silicone oil, and phosphate surfactants.

[0017] Compared with the prior art, the technical effect achieved by adopting this technical solution is: A in the core material includes Li + 、Na + , K + One or more of; M and M' in the core material include Fe 2+ , Fe 3+ 、Ni 2+ , Mn 2+ , Mn 3+ 、Co 3+ 、Zn 2+ , Cu 2+ Cr 3 + Cr 4+ One or more of; M and M' in the core material are transition metal ions in different coordination positions, and the transition metal ion M' is related to cyanide (CN - ) forms a cyanide coordination ion [M'(CN)6] containing a transition metal M'. 3- / 4- In the crystal structure, M is associated with cyanide (CN - ) is coordinated by N.

[0018] In one technical solution of the present invention, the average particle size of the core material is in the range of 1 μm-20 μm; and / or the thickness of the coating layer is in the range of 2 nm-100 nm; and / or the specific surface area of ​​the Prussian blue positive electrode material is in the range of 2 nm-100 nm. 2 / g-8m 2 / g.

[0019] Compared with the prior art, the technical effect achieved by adopting this technical solution is as follows: the average particle size of the core material and the thickness of the coating layer are related to the diffusion rate of ions. When the average particle size of the core material is in the range of 1μm-20μm and the thickness of the coating layer is in the range of 2nm-100nm, it is most conducive to the diffusion of ions.

[0020] Preferably, the specific surface area of ​​the Prussian blue cathode material is measured in the range of 2 m 2 / g-8m 2 / g, a suitable specific surface area can reduce the adsorption capacity of the Prussian blue positive electrode material, avoid further oxidative decomposition reaction, and further avoid the surface of the Prussian blue positive electrode material being covered, so as not to cause excessive energy loss of the Prussian blue positive electrode material, and make the electrochemical energy storage device have better cycle performance; the suitable specific surface area can also ensure that there will be no serious agglomeration between the particles of the Prussian blue positive electrode material, and can effectively shorten the path of ion diffusion, so as to make the electrochemical energy storage device have better rate performance without affecting the cycle performance of the electrochemical energy storage device.

[0021] In one technical solution of the present invention, the moisture growth value △ of the Prussian blue cathode material after being exposed to water absorption at a dew point of -20°C for 72 hours is less than 600 ppm; and / or the contact angle between the Prussian blue cathode material and water is between 140° and 160°.

[0022] Compared with the prior art, the technical effect achieved by adopting the technical scheme is as follows: when the Prussian blue positive electrode material absorbs water for 72 hours at -20°C, the moisture growth value △ is <600ppm, which proves that the secondary water absorption content of the Prussian blue positive electrode material is greatly reduced at this time, that is, before the battery cell is filled with liquid and packaged, the Prussian blue positive electrode material is under the same dew point conditions. The water absorption value of the Prussian blue positive electrode material of the present application will be significantly lower than that of the Prussian blue positive electrode material without a coating layer, thereby effectively reducing the water content of the material in the battery cell, fundamentally avoiding excessive crystallization water, and during the battery cycle, it is deintercalated with the alkali metal ions, thereby coming out of the crystal lattice to react with the electrolyte, reducing the gas production, and improving the battery cycle performance.

[0023] Similarly, the contact angle between the Prussian blue-based cathode material and water ranges between 140° and 160°, indicating that the Prussian blue-based cathode material has good hydrophobic properties, thereby interrupting the conversion process of surface adsorbed water to internal crystalline water, so that the Prussian blue-based composite material not only has a low water content, but also can prevent it from secondary water absorption during use.

[0024] In one technical solution of the present invention, the XRD diffraction peak of the Prussian blue positive electrode material is a single peak at 34°±2°.

[0025] Compared with the prior art, the technical effect achieved by adopting this technical solution is as follows: the intensity of the XRD diffraction peak indicates the relative intensity of the background, that is, in the XRD diffraction peak, the position of the crystallization peak can be used to determine the lattice constant of the crystal. When the XRD diffraction peak is a single peak, the material exhibits a cubic phase, and when it is a double peak, the material exhibits a rhombohedral phase. The rhombohedral phase material has a higher content of alkali metal ions inside the crystal lattice than the cubic phase material. As the sodium content changes, a transformation will occur between the two crystal forms.

[0026] To achieve the second object of the present invention, the present invention provides a method for preparing a Prussian blue positive electrode material, comprising the following steps:

[0027] S100, containing [M′(CN)6] 3- / 4- The salt containing [M′(CN)6] 3- / 4- The salt containing the transition metal ion M and the first complexing agent are dissolved in the solvent to obtain a third solution; the second complexing agent is dissolved in the solvent to obtain a fourth solution;

[0028] S200, under a protective atmosphere, pumping the second solution, the third solution and the fourth solution into the first solution respectively, and sequentially performing an aging treatment, a centrifugal treatment and a primary drying treatment to obtain a core material;

[0029] S300, spraying a coating material on at least a portion of the surface of the core material under a protective atmosphere to obtain a Prussian blue positive electrode material;

[0030] The coating material includes one or more of polysiloxane, ethyl silicone oil, methylphenyl silicone oil, wax-containing silicone oil, cyanide-containing silicone oil, and phosphate surfactant.

[0031] Compared with the prior art, the technical effect achieved by adopting this technical solution is as follows: In this technical solution, firstly, [M′(CN)6] 3- / 4- The salt containing [M′(CN)6] 3- / 4- The salt containing the transition metal ion M is dissolved in a solvent to obtain a second solution; the salt containing the transition metal ion M and the first complexing agent are dissolved in a solvent to obtain a third solution; the second complexing agent is dissolved in a solvent to obtain a fourth solution; the first solution is used as a base liquid, and under a protective atmosphere, the second solution, the third solution and the fourth solution are respectively pumped into the first solution, and the pH value of the reaction process is controlled by adjusting the pumping rate of the fourth solution, and the internal composition of the core material in the Prussian blue positive electrode material during the reaction is controlled by adjusting the pumping rate of the second solution and the third solution; and aging treatment, centrifugation treatment and primary drying treatment are sequentially performed to obtain the core material; the primary drying treatment can dry the adsorbed water on the surface of the material, and reduce part of the crystal water and coordinated water, effectively avoiding the reduction of the sodium content and gram capacity due to the combined water, and significantly improving the energy density of the battery;

[0032] It should be noted that after the core material of the Prussian blue cathode material is dried and a uniform and dense coating layer is constructed on the core surface, the internal crystal water content z is 0≤z≤5, and the Prussian blue cathode material can also be dried without water molecules;

[0033] Subsequently, under a protective atmosphere, the coating material is sprayed on at least part of the surface of the core material, the coating material is deposited on the surface of the positive electrode material and then cross-linked to form a hydrophobic coating layer, and after cooling to room temperature, the Prussian blue positive electrode material of the present application can be obtained; the Prussian blue composite material finally obtained not only has a low water content, but also has a uniform and dense hydrophobic layer coated on the surface, which can prevent the material from absorbing water secondary during use.

[0034] The coating layer includes one or more of polysiloxane, ethyl silicone oil, methylphenyl silicone oil, wax-containing silicone oil, cyanide-containing silicone oil, and phosphate surfactants. On the one hand, since the above materials have hydrophobic and waterproof properties, coating the surface of the core material can make its positive electrode material waterproof and hydrophobic, increase the contact angle between the material and water, from 0° to between 140° and 160°, and reduce the adsorption of moisture on the surface of the material; on the other hand, the use of these coating materials will be evenly coated on the surface of the particles to form a uniform and dense hydrophobic oligomer coating layer. Due to the micro-nano structure characteristics of the surface, the tiny air shield layer hinders the contact between moisture and the core material, thereby interrupting the conversion process of surface adsorbed water to internal crystallized water, so that the crystallization water content of the material is kept within a low range.

[0035] In one technical solution of the present invention, in S100: in the first solution [M′(CN)6] 3- / 4- The concentration of ions is 0.001mol / L-0.4mol / L; and / or the concentration of alkali metal ions A in the first solution is 0.01mol / L-0.7mol / L; and / or the concentration of [M′(CN)6] in the second solution is 3- / 4- The concentration of the ions is 0.1mol / L-0.6mol / L; and / or the concentration of the transition metal ions M in the third solution is 0.1mol / L-1.0mol / L; the concentration of the first complexing agent solution is 0.05mol / L-2.0mol / L; and / or the concentration of the second complexing agent solution is 0.01mol / L-1mol / L.

[0036] Compared with the prior art, the technical effect achieved by adopting this technical solution is that the concentration of the raw materials is related to the particle size, water content and microscopic morphology of the Prussian blue positive electrode material, and thus a preferred range is given, which is beneficial for technical personnel in the field to implement the positive electrode material claimed to be protected by this application.

[0037] In one technical solution of the present invention, in S200: the pumping rate of the second solution is 100mL / h-2500L / h; and / or the pumping rate of the third solution is 50mL / h-1250L / h; and / or the pumping rate of the fourth solution is 5mL / h-200L / h; the pumping temperature is maintained at 30℃-90℃; and / or the aging time is 5h-30h; and / or the aging temperature is 30℃-95℃; and / or the temperature of the primary drying treatment is 80℃-150℃; and / or the time of the primary drying treatment is 5h-30h.

[0038] Compared with the prior art, the technical effect achieved by adopting this technical solution is as follows: by adjusting the flow rate of the solution, the particle size, specific surface area and water content of the Prussian blue positive electrode material are affected, thereby providing an optimal range, which is beneficial for technical personnel in the field to implement and obtain the positive electrode material claimed to be protected by this application.

[0039] In one technical solution of the present invention, in S300: the protective gas is backblown throughout the whole process, and the frequency of backblowing is 1 min / time-5 min / time; and / or the vacuum degree of spraying is not more than 0.09 MPa; and / or the temperature of spraying is 160°C-190°C.

[0040] Compared with the existing technology, the technical effects achieved by adopting this technical solution are as follows: the role of backblowing is to prevent the vacuum exhaust mesh port of the reaction equipment from being blocked, and at the same time provide a protective atmosphere to prevent the core material from being oxidized during the high-temperature drying process; through the temperature and vacuum degree of the spraying, under the condition of vacuum negative pressure, high temperature is applied at the same time to achieve uniform coating on the surface of the particles.

[0041] In a technical solution of the present invention, in S300: before spraying, it also includes: a secondary drying treatment; the temperature of the secondary drying treatment is 150° C.-230° C.; and / or the time of the secondary drying treatment is 5h-30h.

[0042] Compared with the prior art, the technical effect achieved by adopting the technical scheme is as follows: before spraying, the core material is subjected to a secondary drying treatment again, and the secondary drying treatment can allow the internal crystal water and coordinated water to escape as much as possible, so as to obtain a Prussian blue positive electrode material with a low water content and a dense coating layer. The low water content and the ability to inhibit reabsorption of water can significantly inhibit the reaction between the release of crystal water and the electrolyte and the gas production of the battery, thereby extending the battery life and safety; at the same time, under different drying temperature and time conditions, the crystal water and coordinated water content inside the core material lattice are treated to different stages, and finally mixed with the coating material to prepare a Prussian blue positive electrode material containing a coating layer; the secondary drying treatment can prevent water molecules from easily entering the interior of the Prussian blue positive electrode material, so that the material has excellent hydrophobic properties, can significantly inhibit the occurrence of reactions and gas production, and extend the battery life and safety.

[0043] To achieve the third object of the present invention, the present invention further provides a battery, comprising any of the above-mentioned positive electrode materials, and thus including the effects of any of the above-mentioned solutions, which will not be described in detail here.

[0044] After adopting the technical solution of the present invention, the following technical effects can be achieved:

[0045] (1) By constructing a uniform and dense coating layer on the surface of the core material, on the one hand, the contact angle between the material and water can be increased, reducing the surface water adsorption; on the other hand, the dense coating layer interrupts the conversion process of surface adsorbed water to internal crystallized water, thereby reducing the internal crystallized water content; the dew point requirement for moisture in the storage / packaging space is reduced, and a small amount of adsorbed water on the surface can be removed at a lower temperature during the electrode drying stage without considering the impact of the difficulty in removing internal crystallized water on battery performance, thereby effectively reducing the pressure on the cell end to process the electrode water content and reducing the processing cost;

[0046] (2) Under a protective atmosphere, the temperature is raised to obtain low-pressure and high-temperature coating conditions; the coating material will be quickly absorbed into the cone and evenly coated on the surface of the core material to form a uniform and dense hydrophobic oligomer coating layer, thereby removing the surface adsorbed water and preventing the material from absorbing water again during use;

[0047] (3) Before spraying, secondary drying treatment can allow the internal crystal water and coordinated water to escape as much as possible, so as to obtain a Prussian blue positive electrode material with a low water content and a dense coating layer. The low water content and the ability to inhibit reabsorption of water can significantly improve the battery cycle performance and reduce gas production, thereby extending the battery life and safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings to be used in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0049] Figure 1 A schematic diagram of a hydrophobicity experiment of a Prussian blue positive electrode material provided in Example 1 of the present invention and Comparative Example 1;

[0050] Figure 2 A scanning electron microscope (SEM) image of a Prussian blue positive electrode material provided in Example 1 of the present invention and Comparative Example 1;

[0051] Figure 3A scanning electron microscope (SEM) image, element mapping image and element content image of a Prussian blue positive electrode material provided in Comparative Example 1 of the present invention;

[0052] Figure 4 A scanning electron microscope (SEM) image, element mapping image and element content image of a Prussian blue positive electrode material provided in Example 1 of the present invention;

[0053] Figure 5 An X-ray diffraction pattern (XRD pattern) of a Prussian blue cathode material provided in Example 1 of the present invention;

[0054] Figure 6 An X-ray diffraction pattern (XRD pattern) of a Prussian blue cathode material provided in Comparative Example 1 of the present invention;

[0055] Figure 7 This is an X-ray diffraction pattern (XRD pattern) of a Prussian blue positive electrode material provided in Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0056] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

[0057] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0058] In order to make the above-mentioned objects, features and advantages of the present invention more clearly understood, the following Figures 1 to 7 The specific embodiments of the present invention are described in detail.

[0059] Sodium Prussian blue does not require sintering during its synthesis and can be directly synthesized using the co-precipitation method. It does not contain precious metals and is environmentally friendly. As a battery positive electrode material, it has attracted widespread attention due to its lowest cost.

[0060] However, due to the charge balance effect of the Prussian blue compound, M′(CN)6 holes are easily generated in the crystal structure. These holes are often occupied by water molecules, which are called coordinated water. Crystallization water is also inevitably present in the pores within the crystal structure. Crystallization water does not participate in the coordination of transition metals but exists alone in the pores. It also forms hydrogen bonds with the coordinated water, which requires higher energy to break the hydrogen bonds when removing the crystallization water, making it more difficult to completely remove the water. In addition, when the internal holes and pores are filled, some adsorbed water will also exist on the surface. Due to the existence of holes, the material is also very easy to absorb water after water removal.

[0061] According to the difficulty of different types of water in the Prussian blue compound to escape, coordinated water > crystallized water > adsorbed water, the order of water loss can be attributed to removing surface adsorbed water first, then crystallized water, and finally coordinated water; conversely, when the water is completely removed, the material is exposed to an environment with high moisture and its water absorption order can be regarded as the reverse behavior of the water loss order, that is, the water absorption process is a gradual transition from surface adsorbed water to internal crystallized water and coordinated water, and after entering the bulk phase, it exists preferentially in the form of coordinated water.

[0062] The present invention provides a Prussian blue positive electrode material and a preparation method thereof, and a battery. By coating at least part of the surface of a core material with a coating layer, the water contact angle is increased and the water adsorption on the material surface is reduced. At the same time, the coating layer interrupts the conversion process of surface adsorbed water to internal crystal water, thereby reducing the internal crystal water content and reducing the processing cost.

[0063] In the prior art, adsorbed water is often removed by a blast oven. This method can only remove surface adsorbed water and part of the crystallized water in the structure. Therefore, before assembling the battery, the pole piece needs to be treated in a vacuum oven at high temperature and for a long time to remove the crystallized water and coordinated water inside the positive electrode material structure; at the same time, on this basis, an assembly environment with a lower dew point condition needs to be provided to avoid secondary water absorption of the positive electrode material in the pole piece during the battery cell assembly process, which greatly increases the battery cell preparation cost. The present invention provides a method for preparing a Prussian blue positive electrode material, comprising the following steps:

[0064] S100, containing [M′(CN)6] 3- / 4- The salt containing [M′(CN)6] 3- / 4- The salt containing the transition metal ion M and the first complexing agent are dissolved in the solvent to obtain a third solution; the second complexing agent is dissolved in the solvent to obtain a fourth solution;

[0065] S200, under a protective atmosphere, pumping the second solution, the third solution and the fourth solution into the first solution respectively, and sequentially performing an aging treatment, a centrifugal treatment and a primary drying treatment to obtain a core material;

[0066] S300, spraying a coating material on at least a portion of the surface of the core material under a protective atmosphere to obtain a Prussian blue positive electrode material;

[0067] The coating material includes one or more of polysiloxane, ethyl silicone oil, methylphenyl silicone oil, wax-containing silicone oil, cyanide-containing silicone oil, and phosphate surfactant.

[0068] First, the [M′(CN)6] 3- / 4- The salt containing [M′(CN)6] 3- / 4- The salt containing the transition metal ion M is dissolved in a solvent to obtain a second solution; the salt containing the transition metal ion M and the first complexing agent are dissolved in a solvent to obtain a third solution; the second complexing agent is dissolved in a solvent to obtain a fourth solution; the concentration of the raw materials is related to the particle size, water content and microscopic morphology of the Prussian blue positive electrode material, and thus a preferred range is given to facilitate those skilled in the art to obtain the positive electrode material claimed for protection in this application.

[0069] Specifically, in S100: in the first solution [M′(CN)6] 3- / 4- The concentration of the ions is 0.001mol / L-0.4mol / L; and / or the concentration of the alkali metal ions A in the first solution is 0.01mol / L-0.7mol / L; and / or the concentration of the second solution is 0.1mol / L-0.6mol / L; and / or the concentration of the metal ions M in the third solution is 0.1mol / L-1.0mol / L; the concentration of the first complexing agent is 0.05mol / L-2.0mol / L; and / or the concentration of the second complexing agent is 0.01mol / L-1mol / L; A in the core material includes Li + 、Na + , K + and / or the core material M and M' include Fe 2+ , Fe 3+ 、Ni 2+ , Mn 2+ , Mn 3+ 、Co 3+ 、Zn 2+ , Cu 2+ Cr 3+ Cr 4+ One or more of .

[0070] Secondly, the first solution is used as the base liquid, and the second solution, the third solution and the fourth solution are pumped into the first solution respectively under a protective atmosphere, and the pH value of the reaction process is controlled by adjusting the pumping rate of the fourth solution, and the pH value of the solution in the reaction process is adjusted to 5.0-7.5, and the preferred controlled pH value is 6; the internal composition of the core material in the Prussian blue positive electrode material during the reaction is controlled by adjusting the pumping rates of the second solution and the third solution; and aging treatment, centrifugation treatment and primary drying treatment are performed in sequence to obtain the core material; it should be noted that the primary drying treatment can dry the adsorbed water on the surface of the material and reduce part of the crystallized water and coordinated water, so as to facilitate the secondary treatment of the material; at the same time, the concentration of the raw material is related to the particle size, water content and microscopic morphology of the Prussian blue positive electrode material, and thus a preferred range is given, which is beneficial for those skilled in the art to obtain the positive electrode material claimed to be protected by the present application

[0071] Specifically, in S200: in the first solution [M′(CN)6] 3- / 4- The concentration of ions is 0.001mol / L-0.4mol / L; and / or the concentration of alkali metal ions A in the first solution is 0.01mol / L-0.7mol / L; and / or the concentration of the second solution is 0.1mol / L-0.6mol / L; and / or the concentration of metal ions M in the third solution is 0.1mol / L-1.0mol / L; the concentration of the first complexing agent is 0.05mol / L-2.0mol / L; and / or the concentration of the second complexing agent is 0.01mol / L-1mol / L.

[0072] Furthermore, the container selected for pumping in S200 is a reactor; and after the aging treatment, it is necessary to add deionized water for centrifugal washing 3 to 5 times to separate the solid and liquid to obtain a precipitate, and after the precipitate is dried in an oven, it is crushed and sieved to obtain the core material.

[0073] Furthermore, the container selected in S300 is a double-cone rotary vacuum dryer, and the protective gas is backblown throughout the process, with a backblowing frequency of 1 min / time to 5 min / time; the vacuum degree of spraying is not more than 0.09 MPa; and / or the spraying temperature is 160°C-190°C; and before spraying, it also includes: secondary drying treatment; the temperature of the secondary drying treatment is 150°C-230°C; and / or the time of the secondary drying treatment is 5h-30h. Before the mixing treatment, the core material is subjected to a secondary drying treatment. Under different drying temperature and time conditions, the crystal water and coordinated water content inside the core material lattice are processed to different stages;

[0074] Under low pressure and high temperature conditions, the coating material is sprayed on at least part of the surface of the core material, the coating material is deposited on the surface of the positive electrode material and then cross-linked to form a hydrophobic coating layer, and after cooling to room temperature, the Prussian blue positive electrode material of the present application can be obtained; the Prussian blue composite material finally obtained not only has a low water content, but also has a uniform and dense hydrophobic layer on the surface, which can prevent the material from absorbing water secondary during use. The low water content and the ability to inhibit water absorption can significantly inhibit the reaction between the release of crystal water and the electrolyte and the gas production of the battery, thereby extending the battery life and safety.

[0075] It should be noted that the protective atmosphere is a gas with an oxygen content of no more than 0.001%. The protective gas here is mainly used to protect the material and prevent the Prussian blue from being oxidized during the reaction. It also plays a role of backblowing to prevent the exhaust holes of the secondary drying and coating reaction equipment from being blocked, affecting the normal discharge of drying water and the internal pressure during the reaction.

[0076] Furthermore, for the Prussian blue positive electrode material, after the core material is dried and a uniform and dense coating layer is constructed on the core surface, the internal crystalline water content z is 0≤z≤5, or the Prussian blue positive electrode material does not contain water molecules after drying; at the same time, the mixing treatment includes a first mixing treatment and a second mixing treatment. The two-stage mixing treatment allows the coating material to be more evenly coated on the surface of the core material, and the obtained coating layer of the Prussian blue positive electrode material has a higher density.

[0077] Specifically, the material used for the coating layer includes one or more of polysiloxane, ethyl silicone oil, methylphenyl silicone oil, wax-containing silicone oil, cyanide-containing silicone oil, and phosphate surfactants. Among them, polysiloxane includes polydimethylsiloxane, cyclomethylsiloxane, aminosiloxane, polymethylphenylsiloxane, polyether polysiloxane copolymer, and cyclopolydimethylsiloxane.

[0078] Furthermore, the first complexing agent includes one or more of citric acid, citrate, phosphate, ethylenediaminetetraacetate, ammonia water, sodium hydroxide, etc.; the second complexing agent includes one or more of citric acid, citrate, phosphate, ethylenediaminetetraacetate, ammonia water, sodium hydroxide, etc.

[0079] [Example 1]

[0080] This embodiment provides a method for preparing a Prussian blue positive electrode material, comprising the following steps:

[0081] S100, dissolving sodium ferrocyanide and sodium sulfate in deionized water to obtain 10 L of a first solution; dissolving sodium ferrocyanide in deionized water to obtain 10 L of a second solution; dissolving ferrous sulfate and sodium citrate in deionized water to obtain 5 L of a third solution; dissolving citric acid in deionized water to obtain 1 L of a fourth solution;

[0082] Among them, [M′(CN)6] 3- / 4- The concentration of ions is 0.02 mol / L, the concentration of sodium sulfate in the first solution is 0.5 mol / L, and the concentration of [M′(CN)6] in the second solution is 3- / 4- The concentration of the ions is 0.4 mol / L, the concentration of the transition metal ions M in the third solution is 0.8 mol / L, the concentration of the first complexing agent is 0.4 mol / L, and the concentration of the second complexing agent is 0.01 mol / L;

[0083] S200, a protective atmosphere of nitrogen with a gas flow rate of 300 mL / min is introduced into the reactor, and the second solution, the third solution and the fourth solution are pumped into the first solution at 400 mL / h, 200 mL / h and 40 mL / h respectively, and the temperature is maintained at 50°C. After the pH value in the reactor is adjusted to 5.9-6.1 by the pumping rate of the fourth solution, the reaction is completed and the pumping is stopped; then the temperature is raised to 90°C for 24 hours of aging treatment; deionized water is added for centrifugal washing 3 times, and a precipitate is obtained by solid-liquid separation; the precipitate is placed in a common oven at 120°C for 24 hours for a drying treatment to obtain a chemical formula of Na 1.85 Mn[Fe(CN)6] 0.988 •□ 0.012 •1.35H2O core material;

[0084] S300. In a double-cone rotary vacuum dryer, the vacuum degree is 0.09Mpa, and nitrogen backflushing is maintained for 3min / time. The core material is heated to 190°C and dried continuously for 12h. Then 10g of polydimethylsiloxane is sprayed on the surface of the core material. After drying again for 3h, 10g of polydimethylsiloxane is sprayed on the surface of the core material. After completion, the temperature is lowered and the pressure is released to obtain a Prussian blue positive electrode material.

[0085] Among them, the total time of the secondary drying treatment is 15h.

[0086] [Example 2]

[0087] The present embodiment provides a method for preparing a Prussian blue positive electrode material. The specific steps refer to Example 1, except that, in S300, in a double-cone rotary vacuum dryer, the core material is heated to 180°C and continuously dried for 12 hours, and then 10 g of cyclomethylsiloxane is sprayed on the surface of the core material. After drying for 15 hours, 10 g of aminosiloxane is sprayed on the surface of the core material. After completion, the temperature is lowered and the pressure is released to obtain a Prussian blue positive electrode material; wherein the total time for the secondary drying treatment is 27 hours.

[0088] [Example 3]

[0089] The present embodiment provides a method for preparing a Prussian blue positive electrode material. The specific steps refer to Example 1, except that, in S300, in a double-cone rotary vacuum dryer, the core material is heated to 190°C and continuously dried for 12 hours, and then 10 g of polymethylphenylsiloxane is sprayed on the surface of the core material. After drying for 18 hours, 10 g of polyether polysiloxane copolymer is sprayed on the surface of the core material. After completion, the pressure is released to obtain a Prussian blue positive electrode material; wherein the total time for the secondary drying treatment is 30 hours.

[0090] [Example 4]

[0091] The present embodiment provides a method for preparing a Prussian blue positive electrode material. For specific steps, refer to Example 1, except that, in S300, in a double-cone rotary vacuum dryer, the core material is heated to 190°C and dried for 12 hours, and then 10 g of ethyl silicone oil is sprayed on the surface of the core material. After drying for 8 hours, 10 g of methylphenyl silicone oil is sprayed on the surface of the core material. After completion, the pressure is released to obtain a Prussian blue positive electrode material; wherein the total time for the secondary drying treatment is 20 hours.

[0092] [Example 5]

[0093] The present embodiment provides a method for preparing a Prussian blue positive electrode material. The specific steps refer to Example 1, except that, in S300, in a double-cone rotary vacuum dryer, the core material is heated to 190°C and dried for 12 hours, and then 10 g of wax-containing silicone oil is sprayed on the surface of the core material. After drying for 6 hours, 10 g of cyanide-containing silicone oil is sprayed on the surface of the core material, the mixing treatment is completed, the pressure is released, and the Prussian blue positive electrode material is obtained; wherein, the total time for the secondary drying treatment is 18 hours.

[0094] [Example 6]

[0095] The present embodiment provides a method for preparing a Prussian blue positive electrode material. The specific steps refer to Example 1, except that, in S300, in a double-cone rotary vacuum dryer, the core material is heated to 160°C and continuously dried for 12 hours, and then 10g of ethyl silicone oil is sprayed on the surface of the core material. After drying for 4 hours, 10g of ethyl silicone oil is sprayed on the surface of the core material. After completion, the pressure is released to obtain a Prussian blue positive electrode material; wherein the total time for the secondary drying treatment is 16 hours.

[0096] [Comparative Example 1]

[0097] This comparative example provides a method for preparing a Prussian blue positive electrode material. The specific steps are shown in Example 1, except that in S300, the core material is heated to 160° C. and subjected to continuous drying treatment for 18 hours without coating treatment.

[0098] [Comparative Example 2]

[0099] This comparative example provides a method for preparing a Prussian blue positive electrode material. The specific steps are shown in Example 1, except that in S300, the core material is heated to 180°C and subjected to continuous drying treatment for 18 hours without coating treatment.

[0100] [Comparative Example 3]

[0101] This comparative example provides a method for preparing a Prussian blue positive electrode material. The specific steps are shown in Example 1, except that in S300, the core material is heated to 190° C. and subjected to continuous drying treatment for 18 hours without coating treatment.

[0102] [Comparative Example 4]

[0103] This comparative example provides a method for preparing a Prussian blue positive electrode material. The specific steps are shown in Example 1, except that S300 is not included.

[0104] Performance Test:

[0105] Hydrophobicity verification: Place the samples treated in Example 1 and Comparative Example 1 on a dry test bench, respectively, and use a dropper to drop ionized water on the two samples to verify the hydrophobicity of the material. The hydrophobicity can be intuitively determined by the change in the contact angle θ after the water drop contacts the material. Figure 1 As shown;

[0106] Conclusion: The samples treated in Example 1 and Comparative Example 1 were placed on a dry test bench. Figure 1 There is no difference between the two in the optical pictures. Deionized water is added to the two samples with a dropper to verify the hydrophobic property of the material. The contact angle θ increases significantly after the water drop contacts the sample of the embodiment, indicating that the sample has good hydrophobic properties. On the contrary, the contact angle between the sample of comparative example 1 and the water drop is small, and the water drop is quickly absorbed.

[0107] Scanning electron microscope SEM images: The microscopic morphology, element mapping and element content distribution diagram of comparative example 1 and embodiment 1 were respectively photographed and outputted using a scanning electron microscope. Figure 2 shown.

[0108] Conclusion: From Figure 2 The scanning electron microscope (SEM) image of the sample coated with PDMS in Example 1 shows that the actual coating has no effect on the particle morphology, and no obvious impurity particles appear, indicating that the coating agent is distributed on the particle surface.

[0109] Scanning electron microscope SEM images, element mapping and element content diagram: Figure 3 , Figure 4 As shown, Figure 3For comparative example 1, Figure 4 For embodiment 1;

[0110] Conclusion: From Figure 4 The element mapping diagram of the sample coated with PDMS in Example 1 and the element mapping distribution of the main element Si of the coating agent show that the coating layer is evenly distributed on the surface of the particles, and the element content diagram also clearly shows the content of Si element, indicating that PDMS is successfully coated on the surface of the particles; Figure 3 In contrast, there is no Si in Comparative Example 1.

[0111] X-ray diffraction patterns: The crystal structures of Example 1, Comparative Example 1 and Comparative Example 4 were tested using an X-ray diffractometer. Figure 5-Figure 7 As shown, Figure 5 For Example 1, Figure 6 For comparative example 1, Figure 7 This is comparative example 4.

[0112] Conclusion: The X-ray diffraction patterns (XRD) of Example 1 and Comparative Example 1 show no impurity peaks, indicating that the coating layer is evenly coated on the particle surface and no impurities are generated. Compared with Comparative Example 4, the main diffraction peak position of Example 1 has not changed, indicating that the material after water removal and coating still exhibits a rhombohedral phase structure; the weakening of the peak intensity is mainly attributed to the release of crystal water in the organic metal framework, which causes the crystal shape to deteriorate;

[0113] The water content of the samples of different embodiments and comparative examples after dehydration treatment and exposure to a dew point of -20°C for 72 hours was characterized using a Karl Fischer titrator, and the test cutoff temperature of the water content was 170°C. The results of the water content test are shown in Table 1.

[0114] The positive electrode material particles of the above-mentioned embodiment and comparative example are prepared into positive electrode sheets, and assembled into button batteries, and the operation steps are as follows:

[0115] The positive electrode material, acetylene black and polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 90:5:5, mixed evenly, added with an appropriate amount of NMP and stirred for 2 hours to form a viscous slurry, which was evenly coated on an aluminum foil with a thickness of 15 μm, and then vacuum-baked at 80°C, pressed into sheets, and cut into positive electrode discs with a diameter of 14 mm.

[0116] A pure sodium sheet with a diameter of 16 mm was used as the negative electrode sheet, Tianci's ENA-26A was used as the electrolyte, and a PP / PE / PP composite diaphragm was used to assemble the button-type battery in a glove box filled with argon.

[0117] The first discharge capacity, first efficiency, and cycle capacity retention rate of the button cells of the above-mentioned embodiment and comparative example were tested, and the operation steps were as follows:

[0118] The voltage range is 2v-4v, the nominal gram capacity is 150mAh / g, and the specific test process is: 0.1 / 0.1C charge and discharge for two weeks, and the constant voltage cut-off current is 0.05C; the test obtains the charge and discharge gram capacity, calculates the first efficiency, and the results are shown in Table 1.

[0119] The positive electrode material particles of the above-mentioned embodiment and comparative example are prepared into positive electrode sheets and assembled into a full battery, and the operation steps are as follows:

[0120] The positive electrode material, conductive carbon black SP, conductive graphite KS-6, and binder PVDF are mixed in a mass ratio of 92%: 4%: 1%: 3%, and an appropriate amount of NMP (N-methylpyrrolidone) is added to make a positive electrode slurry, which is made into a positive electrode sheet through coating and rolling processes. The positive electrode sheet is assembled with the negative electrode (hard carbon), separator, and electrolyte (1mol / L•NaPF6+DEC / EC (volume ratio 1:1)) into a 503048 model full battery with a battery capacity of about 400mAh, which is used for testing.

[0121] Cycle performance test: using Xinwei test cabinet (CT3008-5V3A-A1), at 25℃, cycle voltage 1.5V-3.8V, constant voltage cut-off current 20mA, cycle 300 times.

[0122] Thermal runaway gas production test at 45°C for 7 days. The results are shown in Table 1.

[0123] Table 1

[0124] project After water removal / (ppm) Water value after exposure to -20℃ dew point for 72h / (ppm) Difference / (ppm) First discharge capacity / (mAh / g) First effect / % 300 cycles at 25°C Capacity retention rate / % 7 days 45℃ thermal gas production / % Example 1 1632 2038 406 156.2 97.6 96.7 1.2 Example 2 5352 5942 590 155.1 94.8 88.2 3.2 Example 3 1675 2236 561 154.3 97.2 93.4 1.6 Example 4 1687 2185 498 157.4 96.8 92.6 1.4 Example 5 1653 2225 572 156.3 97.5 91.2 1.7 Example 6 25231 25683 452 154.8 93.8 68.7 5.6 Comparative Example 1 24569 98785 74216 147.8 92.8 43.8 8.8 Comparative Example 2 5679 96735 91056 150.3 93.7 53.8 6.8 Comparative Example 3 1468 98653 97185 152.1 94.5 63.2 5.4 Comparative Example 4 - 105672 - 146.3 90.3 20.3 28.4

[0125] From the moisture test results in Table 1, it can be seen that the embodiments coated with PDMS as the hydrophobic layer all show good resistance to re-absorption of water. Compared with the unexposed samples, the water content re-absorption value of the material after exposure to a dew point of -20°C for 72 hours is <600ppm, showing excellent resistance to water absorption; while the comparative example 1 re-absorbs water to a value close to that before water removal, indicating that spatial water continuously enters the interior of the lattice and is converted from adsorbed water back to interstitial water and lattice water.

[0126] At the same time, compared with comparative examples 1-4, the positive electrode materials of examples 1-6 showed higher first-cycle discharge capacity, first-cycle charge and discharge efficiency, cycle capacity retention rate and lower thermal runaway gas production, showing very excellent electrochemical performance. This is mainly due to the good ability of the hydrophobic layer to inhibit water reabsorption, which makes the water content of the pole piece lower when assembling the battery; the obvious reduction in gas production significantly improves the safety and practicality of the battery.

[0127] In summary, the present invention provides a feasible solution for preventing the secondary reabsorption of water during use of Prussian blue analogs after removing coordinated water and crystal water.

[0128] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A Prussian blue positive electrode material, characterized in that: The Prussian blue positive electrode material comprises a core material and a coating layer coated on at least a portion of the surface of the core material: The chemical formula of the core material is A x M[M′(CN)6] 1–y •□ y •zH2O, A is an alkali metal ion; M and M' are transition metal ions; □ is [M'(CN)6] 3- / 4- Hole; H2O is coordinated water; 0 <x≤2;0<y≤0.25;0≤z≤5; The coating layer includes a cross-linked oligomer and a cross-linked phosphate surfactant, wherein the oligomer includes one or more of ethyl silicone oil, methylphenyl silicone oil, wax-containing silicone oil, and cyanide-containing silicone oil; Wherein, the Prussian blue positive electrode material has a single crystal-like morphology, and the mass ratio of the coating layer to the core material is (0.005-0.05):1; The average particle size of the core material ranges from 1 μm to 20 μm; The thickness of the coating layer ranges from 2nm to 100nm; The Prussian blue positive electrode material is exposed to water absorption at a dew point of -20°C for 72 hours, and the moisture growth value △ is less than 600ppm; The contact angle between the Prussian blue cathode material and water is between 140° and 160°; The specific surface area of ​​the Prussian blue cathode material is tested in the range of BET of 2 m 2 / g-8m 2 / g.

2. The Prussian blue positive electrode material according to claim 1, characterized in that A in the core material includes Li + 、Na + , K + One or more of; and / or The M and M' in the core material include Fe 2+ , Fe 3+ 、Ni 2+ , Mn 2+ , Mn 3+ 、Co 3+ 、Zn 2+ , Cu 2+ Cr 3+ Cr 4+ One or more of .

3. The Prussian blue positive electrode material according to claim 1, characterized in that The XRD diffraction peak of the Prussian blue positive electrode material is a single peak at 34°±2°.

4. A method for preparing a Prussian blue cathode material, the method being used to prepare the Prussian blue cathode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S100, containing [M′(CN)6] 3- / 4- The salt containing [M′(CN)6] 3- / 4- The salt containing the transition metal ion M and the first complexing agent are dissolved in the solvent to obtain a third solution; the second complexing agent is dissolved in the solvent to obtain a fourth solution; S200, under a protective atmosphere, pumping the second solution, the third solution and the fourth solution into the first solution respectively, and sequentially performing an aging treatment, a centrifugal treatment and a primary drying treatment to obtain a core material; S300, spraying a coating material on at least a portion of the surface of the core material under a protective atmosphere to obtain the Prussian blue positive electrode material; The coating material includes one or more of ethyl silicone oil, methylphenyl silicone oil, wax-containing silicone oil, cyanide-containing silicone oil, and phosphate surfactant.

5. The method for preparing a Prussian blue positive electrode material according to claim 4, characterized in that: In S100: In the first solution, [M′(CN)6] 3- / 4- The concentration of ions is 0.001 mol / L-0.4 mol / L; and / or The concentration of alkali metal ions A in the first solution is 0.01 mol / L-0.7 mol / L; and / or In the second solution, [M′(CN)6] 3- / 4- The concentration of ions is 0.1 mol / L-0.6 mol / L; and / or The concentration of transition metal ions M in the third solution is 0.1 mol / L-1.0 mol / L; The concentration of the first complexing agent solution is 0.05 mol / L-2.0 mol / L; and / or The concentration of the second complexing agent solution is 0.01 mol / L-1 mol / L.

6. The method for preparing a Prussian blue positive electrode material according to claim 4, characterized in that: In S200: The pumping rate of the second solution is 100 mL / h-2500 L / h; and / or The pumping rate of the third solution is 50mL / h-1250L / h; and / or The pumping rate of the fourth solution is 5mL / h-200L / h; The pumped temperature is maintained at 30°C-90°C; and / or The aging treatment time is 5h-30h; and / or The temperature of the aging treatment is 30°C-95°C; and / or The temperature of the primary drying treatment is 80°C-150°C; and / or The time of the primary drying treatment is 5h-30h.

7. The method for preparing a Prussian blue positive electrode material according to claim 4, characterized in that: In S300: The protective gas is backflushed throughout the whole process, and the frequency of the backflushing is 1 min / time to 5 min / time; and / or The vacuum degree of the spraying is not more than 0.09MPa; and / or The spraying temperature is 160°C-190°C.

8. The method for preparing a Prussian blue positive electrode material according to claim 4, characterized in that: In S300: The spraying process also includes: secondary drying process; The temperature of the secondary drying treatment is 150°C-230°C; and / or The secondary drying process takes 5 hours to 30 hours.

9. A battery, characterized in that: The positive electrode material of the battery is the Prussian blue positive electrode material according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Prussian blue composite positive electrode material and preparation method and application thereof

    CN115863564A

  • Hydrophobic polymer coated modified sodium battery positive electrode material, preparation method and battery

    CN115954447A

  • Positive electrode material, preparation method thereof and sodium ion battery

    CN116864656A